Planetary sleep medicine: Studying sleep at the individual, population, and planetary level - Bragazzi, Nicola Luigi; Garbarino, Sergio; Puce, Luca; Trompetto, Carlo; Marinelli, Lucio; Currà, Antonio; Jahrami, Haitham; Trabelsi, Khaled; Mellado, Bruce; Asgary, Ali; Wu, Jianhong; Kong, Jude Dzevela (Frontiers in Public Health, 2022)
Circadian rhythms are a series of endogenous autonomous oscillators that are generated by the molecular circadian clock which coordinates and synchronizes internal time with the external environment in a 24-h daily cycle (that can also be shorter or longer than 24 hours). Besides daily rhythms, there exist as well other biological rhythms that have different time scales, including seasonal and annual rhythms. Circadian and other biological rhythms deeply permeate human life, at any level, spanning from the molecular, subcellular, cellular, tissue, and organismal level to environmental exposures, and behavioral lifestyles. Humans are immersed in what has been called the “circadian landscape", with circadian rhythms being highly pervasive and ubiquitous, and affecting every ecosystem on the planet, from plants to insects, fishes, birds, mammals, and other animals. Anthropogenic behaviors have been producing a cascading and compounding series of effects, including detrimental impacts on human health. However, the effects of climate change on sleep have been relatively overlooked. In the present narrative review paper, we wanted to offer a way to re-read/re-think sleep medicine from a planetary health perspective. Climate change, through a complex series of either direct or indirect mechanisms, including i) pollution- and poor air quality-induced oxygen saturation variability/hypoxia, ii) changes in light conditions and increases in the nighttime, iii) fluctuating temperatures, warmer values, and heat due to extreme weather, and iv) psychological distress imposed by disasters (like floods, wildfires, droughts, hurricanes, and infectious outbreaks by emerging and reemerging pathogens) may contribute to inducing mismatches between internal time and external environment, and disrupting sleep, causing poor sleep quantity and quality and sleep disorders, such as insomnia, and sleep-related breathing issues, among others. Climate change will generate relevant costs and impact more vulnerable populations in underserved areas, thus widening already existing global geographic, age-, sex- and gender-related inequalities.